Pengaruh Ulasan Pelanggan, Kepercayaan Dan Promosi Terhadap Keputusan Pembelian Menggunakan Shopee Barokah - Tasia Lailatul Saputri; Ika Septiana Windi Antari (Niqosiya: Journal of Economics and Business Research, 2026)
Introduction: This study is about how customer reviews, trust and promotions can influence a purchasing decision using shopee barokah. Shopee barokah is a shopping feature that provides halal products in accordance with sharia principles ranging from halal food and drinks, prayer equipment, muslim clothing to Islamic literature. The launch of shopee barokah is based on one of the trends regarding public awareness of the importance of halal products. This trend is also in line with Indonesia’s ambition to become a leader in the halal sector globally. From the existing theory, it is stated that the higher the customer review, the higher the purchasing decision. Meanwhile, if trust and promotion are higher, the purchasing decision will also be higher. Research Methods: This study uses associative quantitative research methodology. The population in this study were shopee barokah users with a sample size of 100 shopee barokah user respondents. In this study, the sampling technique used was simple random sampling where each member of the population has an equal opportunity to be a sample. Data collection procedure by distributing questionnaires. Data analysis was carried out using the SMART PLS 4.0 application which includes outer model, inner model and hypothesis testing. Results: Based on the research above, it was found that the research model used was Partial Least Square (PLS) with the results of all tests having been met. Conclusion: The results of this study can be concluded partially that customer reviews have a positive effect on purchasing decisions, trust has a positive effect on purchasing decisions and promotion has a positive effect on purchasing decisions. Meanwhile, customer reviews, trust and promotion simultaneously also have a positive effect on purchasing decisions.